The Construction of Security: Challenges and Options for Bangladesh - Khan, Md. Azmal Mahmud (The Jahangirnagar Review Part-C, 2024)
: In the global political structure, security is the primary concern of every state. There are many parameters to determine the concept of security and methods to achieve security. Though the approaches vary from country to country, the underlying goal remains the same. Availability of resources is of paramount importance to ensure security. The more resourceful states enjoy significant flexibility in the formulation and implementation of security policy while the scenario for the less resourceful is precisely the opposite. As a small and developing country, Bangladesh has been troubled to formulate its security policy addressing all sorts of security threats simultaneously. As a result, it is important to formulate a policy which would suit best to preserve the national interest. This paper analyzes the construction of security concept, prevailing global practices, identify the challenges to Bangladesh and possible ways to ensure security and promote position in the current global political environment.